IMPACT OF DIFFERING CONCENTRATE INCLUSION LEVELS ON THE GROWTH PERFORMANCE OF WEANED LAMBS - Rodriguez , Angela Maria; Williams, Samuel James (Advanced Journal of Environmental Sciences (AJES), 2023)
In Trinidad and Tobago, the productivity of small ruminant livestock faces several challenges, including inadequate reproductive strategies, genetic stock, and veterinary services. However, the most critical factor limiting productivity is the poor feed supply and feeding system, given that the available feed resources mainly consist of natural pastures and crop residues. These feed sources are characterized by high fibrous content, lignin levels, and low nutritive value. Animals consuming low-quality feed deplete their fat reserves to meet nutrient requirements, resulting in reduced fat storage, particularly during dry forage growth periods and extended underfeeding. Livestock’s live weight and nutritional status significantly impact production efficiency metrics like feed conversion ratio (FCR) and average daily gain (ADG). Most dry forages and roughages in the region have crude protein (CP) content below 7%, making it challenging to meet microbial requirements without protein-rich supplementation. Feeding poor-quality forage alone cannot even fulfill maintenance requirements for livestock. Therefore, improving the feeding system for small ruminants becomes imperative, with a focus on supplementing grass with high-energy feeds. One promising approach to enhance the nutritive value of crop residues involves strategic supplementation with energy and protein-rich sources, promoting voluntary feed intake, digestibility, and utilization. This study underscores the importance of such supplementation strategies to address the pressing issue of low small ruminant productivity in Trinidad and Tobago.